An Integration of Education and Economic Empowerment in Da'wah Strategies: A Case Study of Mualaf in the Dayak Meratus Tribe - Mz, Ihsan; Marhani, Isnaeni; Yanuri, Yusuf R.; Pranajaya, Syatria Adymas (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2025)
This study aims to analyze the da'wah model implemented within the Dayak Meratus tribe in South Kalimantan, focusing on the provision of scholarships and economic empowerment. Da'wah in this community plays a significant role in enhancing religious understanding and improving the quality of life. The research adopts a descriptive qualitative approach, utilizing in-depth interviews and direct observation as data collection methods. The research was conducted in several areas inhabited by the Dayak Meratus tribe, with subjects comprising mualaf, religious leaders, and policymakers involved in economic empowerment programs. The findings indicate that the provision of scholarships for education and collaboration with multiple stakeholders has had a positive impact on the increase in the number of mualaf and the socio-economic welfare of the community. The family-based guidance approach and the frequency of meetings have proven effective in maintaining the commitment of converts to Islam. Furthermore, economic empowerment has made a significant contribution to strengthening their integration into the Muslim community. The discussion highlights that the success of da'wah is heavily influenced by the combination of educational support, economic empowerment, and sustainable social approaches. The conclusion of this study is that a holistic da'wah strategy, combining education and economic empowerment, is highly effective in increasing the number of converts and improving their quality of life. Recommendations for future research include expanding the scope of the study area and involving more variables that influence the success of da'wah within indigenous communities. Penelitian ini bertujuan untuk menganalisis model dakwah yang diterapkan di suku Dayak Meratus, Kalimantan Selatan, dengan fokus pada pemberian beasiswa dan pemberdayaan ekonomi. Dakwah di komunitas ini memiliki peran penting dalam meningkatkan pemahaman agama dan kualitas hidup masyarakat. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan wawancara mendalam dan observasi langsung sebagai metode pengumpulan data. Lokasi penelitian berada di beberapa wilayah yang dihuni oleh masyarakat Dayak Meratus, dengan subjek yang terdiri dari mualaf, tokoh agama, dan pemangku kebijakan yang terlibat dalam pemberdayaan ekonomi umat. Hasil penelitian menunjukkan bahwa pemberian beasiswa untuk pendidikan dan kerjasama dengan banyak stakeholder telah memberikan dampak positif terhadap peningkatan jumlah mualaf dan kesejahteraan sosial-ekonomi masyarakat. Pembinaan yang berbasis pada pendekatan keluarga dan intensitas pertemuan terbukti efektif dalam menjaga komitmen mualaf terhadap Islam. Selain itu, pemberdayaan ekonomi memberikan kontribusi besar dalam memperkuat integrasi mereka ke dalam masyarakat Islam. Diskusi ini mengemukakan bahwa kesuksesan dakwah sangat dipengaruhi oleh kombinasi antara dukungan pendidikan, pemberdayaan ekonomi, dan pendekatan sosial yang berkelanjutan. Kesimpulan dari penelitian ini adalah bahwa strategi dakwah yang holistik, yang menggabungkan pendidikan dan pemberdayaan ekonomi, sangat efektif dalam meningkatkan jumlah mualaf dan kualitas hidup mereka. Rekomendasi untuk penelitian selanjutnya adalah memperluas cakupan wilayah dan melibatkan lebih banyak variabel yang mempengaruhi keberhasilan dakwah dalam komunitas adat.